2000
DOI: 10.14411/eje.2000.052
|View full text |Cite
|
Sign up to set email alerts
|

Host-instar selection in the aphid parasitoid Monoctonus paulensis (Hymenoptera: Braconidae, Aphidiinae): a preference for small pea aphids

Abstract: Abstract. Monoctonus paulensis is a solitary parasitoid of several species of aphids, including the pea aphid, Acyrthosiphon pisum. We evaluated host-instar selection by comparing the parasitoid's preference for the four nymphal instars of the pea aphid, presented two at a time in dichotomous choice tests. Females parasitized more, and laid more eggs in, the relatively smaller aphids among those available. This preference was independent of aphid instar: L1 > L2 > L3 > L4. Preference was not influenced by fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
4
38
1
2
Order By: Relevance
“…This supported previous findings demonstrating that H. axyridis is the most aggressive and better defended species among coccinellid guild (Michaud 2002;Sato et al 2005;Snyder et al 2004;Yasuda et al 2001Yasuda et al , 2004 and that young stages are less defensive than adults against parasitoids (Chau and Mackauer 2000;Gerling et al 1990;Mackauer et al 1996;Walker and Hoy 2003). We demonstrated that H. axyridis could express behavioral defenses not only against predators of the same guild, but also against parasitoids.…”
Section: Host Defenses Occurrence and Effectsupporting
confidence: 93%
“…This supported previous findings demonstrating that H. axyridis is the most aggressive and better defended species among coccinellid guild (Michaud 2002;Sato et al 2005;Snyder et al 2004;Yasuda et al 2001Yasuda et al , 2004 and that young stages are less defensive than adults against parasitoids (Chau and Mackauer 2000;Gerling et al 1990;Mackauer et al 1996;Walker and Hoy 2003). We demonstrated that H. axyridis could express behavioral defenses not only against predators of the same guild, but also against parasitoids.…”
Section: Host Defenses Occurrence and Effectsupporting
confidence: 93%
“…Deste modo, outros fatores a serem considerados na interação entre pulgões e parasitóides são os critérios para escolha de hospedeiro entre espécies de pulgões, segundo seu tamanho ou estágio de desenvolvimento e sua influência no tamanho dos parasitóides adultos (Shu-Sheng & Carver 1985, Godfray 1994, Chau & Mackauer 2000. Como o tamanho pode ser um bom indicador de aptidão ou fecundidade, determinar hospedeiros que maximizem os tamanhos dos inimigos naturais pode ser um elemento importante na estruturação e viabilização de programas de controle biológico ou de manejo integrado de pragas.…”
unclassified
“…because of their size-dependent apparency (van Alphen & Drijver, 1982) or behavioural defence (van Alphen & Drijver, 1982;Brodeur et al, 1996;Harvey, 1996;Chau & Mackauer, 2000), or agedependent survival in hosts (especially koinobiont parasi toids: Driessen et al, 1991;Sequeira & Mackauer, 1994;Brodeur & Vet, 1995). Although this study did not address the question of the causes of the non-selective host use, we would like to highlight a potential explana tion specific to the system studied.…”
Section: Discussionmentioning
confidence: 95%